Real-world efficacy and safety of PD-1 inhibitors in patients with advanced esophageal squamous cell carcinoma: a single-center retrospective analysis - Wang, Xin; Jia, Lili; Zhao, Yijian; Wang, Qinqin; Zhou, Yang; Wang, Yu; Zhang, Xialu; Zhai, Miaoxu; Ren, Yinghong (Frontiers in Oncology, 2025)
BackgroundEsophageal squamous cell carcinoma (ESCC) is associated with high mortality and limited treatment options. While PD-1/PD-L1-targeted immunotherapy has shown promise, clinical trial results may not fully represent real-world outcomes.MethodsThis retrospective study at Shangluo Central Hospital analyzed 116 patients with ESCC treated with PD-1 inhibitors from April 2021 to December 2023. Data were collected from electronic records to assess clinical outcomes, including overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR), as well as factors associated with treatment response and toxicity.ResultsThe cohort had a median age of 66 years, with 86.2% male patients and 71.5% smokers. The majority of patients had advanced disease (stage III: 49.1%, stage IV: 29.3%). The ORR was 40.5%, with 1.7% achieving complete response and 38.8% partial response. The DCR was 81%. The median PFS was 13.6 months, and the median OS was not reached. Better outcomes were associated with age <70 years, ECOG performance status 0/1, fewer than two metastatic organs, and first-line treatment. Treatment-related adverse events (TRAEs) were reported in 10 out of 116 patients (8.6%). Grade ≥3 TRAEs occurred in 4 patients (3.4%), including cutaneous capillary hemangioma (n=3, 2.6%) and dyspnea (n=1, 0.9%). No treatment-related deaths were reported.ConclusionsIn this real-world cohort, PD-1 inhibitors demonstrated notable efficacy and manageable toxicity for ESCC. Younger patients, those with better performance status, and fewer metastases achieved better outcomes. Larger, multi-center studies with biomarker analysis are warranted to validate these findings.